Association between cannabis use and complications related to ulcerative colitis in hospitalized patients: A propensity matched retrospective cohort study. Issue 32 (August 2019) - Mbachi, Chimezie; Attar, Bashar; Oyenubi, Olamide; Yuchen, Wang; Efesomwan, Aisien; Paintsil, Isaac; Madhu, Mathew; Ajiboye, Oyintayo; Simons-Linares, C. Roberto; Trick, William E.; Kotwal, Vikram
Abstract : Abstract: Ulcerative colitis (UC) is a chronic inflammatory process that is occasionally associated with complications that cause significant morbidity and mortality. Studies in experimental animal models have demonstrated a beneficial effect of cannabis on intestinal inflammation. It is however unknown if this corresponds to fewer complications for patients with Ulcerative Colitis. We aimed to compare the prevalence of UC related complications and certain key clinical endpoints among cannabis users and nonusers hospitalized with a primary diagnosis of UC, or primary diagnosis of a UC-related complication with a secondary diagnosis of UC. Using data from the Healthcare Cost and Utilization Project-National Inpatient Sample (NIS) during 2010–2014, a total of 298 cannabis users with UC were compared to a propensity score matched group of nonusers with UC. We evaluated several UC-related complications and clinical endpoints. Within our matched cohort, prevalence of partial or total colectomy was lower in cannabis users compared to nonusers (4.4% vs 9.7%, P  = .010) and there was a trend toward a lower prevalence of bowel obstruction (6.4% vs 10.7%, P  = .057). Cannabis users had shorter hospital length-of-stay (4.5 vs 5.7 days P  < .007) compared to their nonuser counterparts. Cannabis use may mitigate some of the well described complications of UC among hospitalized patients. Our findings need further evaluation, ideally through more rigorous clinical trials.